Sales Multiplize Through E-Commerce Training For Batik Craftsman In Paiton Probolinggo - Sugito, Pudjo (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Batik Craftsmen in Paiton Probolinggo as a business entity for the cultural heritage of the archipelago has to handle challenges that arise as a consequence of increasing competition. The marketing strategy must be carried out as well and as effectively as possible. One option is to apply an online strategy with e-commerce media which is presently the best answer for all business entities. This is due to infrmation through internet media is more effective to meet buyers in terms of informing or marketing their products without having to meet face to face. E-commerce creates it simple for consumers and producers to do business. Therefore, target of this program is to build e-commerce skills of these batik craftsmen. Technique for implementing the activities consists of a participatory approach with the local industry and trade office, e-commerce training and ends with a simulation and evaluation. Based on the evaluation analyisis of the training execution, it was revealed that the positive response of Batik Paiton craftsmen and through periodic assistance has given hope for business continuity. Even sales then experienced a lot of increase, which is very likely as an implication of the wider reach of marketing areas through e-commerce.